Production of wheat gluten hydrolysates with reduced antigenicity employing enzymatic hydrolysis combined with downstream unit operations. (27th November 2015) - Merz, Michael; Kettner, Lucas; Langolf, Emma; Appel, Daniel; Blank, Imre; Stressler, Timo; Fischer, Lutz
Abstract: BACKGROUND: Due to allergies or other health disorders a certain segment of the population is not able to safely consume some plant proteins, which are the main protein support in human nutrition. Coeliac disease is a prominent autoimmune disorder and requires a strict adherence to a gluten‐free diet. The aim of this study was to identify suitable combinations of enzymatic hydrolysis and common unit operations in food processing (centrifugation, ultra‐filtration) to produce gluten‐free wheat gluten hydrolysates for food application. To analyse the hydrolysates, a simple and cheap competitive ELISA protocol was designed and validated in this study as well. RESULTS: The competitive ELISA was validated using gliadin spiked skim milk protein hydrolysates, due to the latter application of the assay. The limit of quantification was 4.19 mg kg −1, which allowed the identification of gluten‐free (<20 mg kg −1 ) hydrolysates. Enzymatic hydrolysis, including the type of peptidase, and the downstream processing greatly affected the antigenicity of the hydrolysates. CONCLUSION: Enzymatic hydrolysis and downstream processing operations, such as centrifugation and ultra‐filtration, reduced the antigenicity of wheat gluten hydrolysates. Gluten‐free hydrolysates were obtained with Flavourzyme after centrifugation (25 g L −1 substrate) and after 1 kDa ultra‐filtration (100 g L −1 substrate). A multiple peptidase complex, such as Flavourzyme, seems to be required for the production of gluten‐free hydrolysates. © 2015 Society of Chemical Industry